The impact of prior stock market reactions on risk taking in acquisitions - Kumar, M. V. Shyam; Dixit, Jaya; Francis, Bill (Strategic Management Journal, 2015)
We study the relationship between the stock market's reaction to a prior acquisition and the risk associated with a subsequent acquisition. Using a sample of 823 acquisitions over the period 1990–2006 we find that acquirers buy increasingly volatile targets both as the abnormal dollar gains from the previous acquisition announcement increase, and as the abnormal dollar losses increase (i.e. a V shaped relationship). Our findings are consistent with psychological theories of decision making and risk seeking, including prospect theory and the house money effect. In addition, they highlight that the stock market reaction to the prior acquisition announcement acts as an important reference point in acquisition decisions . Copyright © 2014 John Wiley & Sons, Ltd.